Ileal and colonic Crohn's disease: Does location makes a difference in therapy efficacy? - Atreya, Raja; Bojarski, Christian; Kühl, Anja A.; Trajanoski, Zlatko; Neurath, Markus; Siegmund, Britta (Current Research in Pharmacology and Drug Discovery, 2022)
Within the IBD entity of Crohn's disease, there is currently no differentiation between ileal and colonic manifestation for recruitment of patients in clinical trials, well-powered analysis of study results or therapeutic decisions in daily clinical practice. However, there is accumulating evidence from epidemiological, genetic, microbial, immunological, and clinical characteristics that clearly indicate that ileal Crohn's disease represents a distinct disease entity, which differentiates itself from colonic Crohn's disease. This is also reflected by lower efficacy of targeted therapies in isolated ileal compared to colonic Crohn's disease. The distinct site-specific mechanisms that drive heightened non-response in ileal disease need to be analysed in-depth in the future, to enable optimized therapy in the individual Crohn's disease patient.
CRIS-Team Scopus Importer:2022-04-08
Keywords: Colonic Crohn's disease; Crohn's disease; Ileal Crohn's disease; Segment; Therapy